Mandatory Reporting on Corporate Social Responsibility (CSR) as A Multinational Corporate Accountability Contemplate (Case Study at PT. Pertamina (Persero)) - Farid Fajrin; Megawati Ismail; Umi Handayani; Nur Indah Sari; Herni Herni (JURNAL PENELITIAN EKONOMI DAN AKUNTANSI (JPENSI), 2022)
The purpose of this study is to examine how PT. Pertamina (Persero), a state-owned firm engaged in the exploration and production of oil, gas, and geothermal energy in Indonesia, has implemented mandatory CSR reporting as a forum for accountability. This is a library research project in which data is collected in the form of journals, books, documents, and other relevant textual sources, which are then descriptively examined and conclusions drawn based on the issues discussed. According to the findings, PT Pertamina (Persero) has completed statutory CSR reporting in the form of an annual report and a sustainability report, both of which are available on the company's official website. PT Pertamina also continues to develop in relation to CSR activities that have a broad positive impact in order to increase corporate accountability. The four pillars of CSR and PKBL, Pertamina Hijau, Pertamina Sehat, Pertamina Cerdas, and Pertamina Berdikari, which encompass social, economic, educational, health, and environmental issues, demonstrate this. It is intended that through implementing these initiatives, they will be able to deliver useful services to the community while also benefiting the national economy.